Medición del nivel de satisfacción de los clientes de la cooperativa de ahorro y crédito Quilanga Ltda. del cantón Quilanga, provincia de Loja, para el año 2016. - Yaguana Japón, Mary Elizabeth (2018)
The general objective of this research is to determine the level of satisfaction of the clients of the Cooperativa de Ahorro y Crédito Quilanga Ltda. Of the canton Quilanga, province of Loja, for the year 2016 ", which served as a means to know the high existing relationship between the client and the management carried out by the organization to enhance its long-term profitability. During the development of the research the inductive, deductive, descriptive, analytical and synthetic methods were used, which allowed to base its development to determine and analyze the factors that led to assess the compliance received by the clients with the service they receive in the entity. Consequently, research techniques were applied, such as: the interview with the manager that was the basis for continuing with the execution of the surveys of internal and external clients to examine in a precise manner the most important aspects of the service offered by the institution and the difficulties presented in it. In compliance with the stated objective, a process was carried out that began with the description of the results obtained with the techniques performed and that allowed for the diagnosis of the clients, for which the Servperf analysis was carried out, which made it possible to determine a regular average level of satisfaction. in internal customers corresponding to 3.60 and 3.92 for external customers. Consecutively, the comparative analysis of the weighted average that was reached in the Servperf analysis with respect to the five factors of tangible elements, reliability, responsiveness, security and empathy was made through the Pearson correlation coefficient; this resulted in a moderate positive correlation of 0.65 representing a service that does not meet all of the client's expectations and does not satisfy it efficiently. Based on the Servperf analysis of the external clients, a factorial analysis applied to the weights obtained by the 22 questions from the previously completed survey was made, from which it was established that there is greater satisfaction in the factor of tangible elements with 98.30% ; while those of reliability with 47% and responsiveness with 33.51% have the lowest level, representing a total level of satisfaction of 64.86% and which does not exceed the 85% average. Consequently, before this result an improvement plan was formulated for the satisfaction of the clients that included the proposition of some activities in the states of risk, preventive and satisfactory, for its execution with the purpose of contributing to solve the situation with reference to the compliance goals indicated for each action and whose investment cost is $ 9605.35. Finally, giving coherence to the above, it could be concluded that the service provided by the staff of this financial institution does not optimize the satisfaction of their customers, so it is advisable to implement the improvement plan immediately. main means that allows them to increase their recognition in them and expand their market in the locality.